Impact of Rural E-Commerce on Farmers’ Income and Income Gap - Xin Guan; Lei He; Zhiquan Hu (Agriculture)
Rural e-commerce, as a new form of digital economy, is of great significance in promoting the income of rural households and realizing common prosperity. Based on the 2021 China Rural Revitalization Survey (CRRS), the impact of rural e-commerce on farmers’ income and the intra-rural income gap is explored using quantile regression. The results found that (1) rural e-commerce can effectively promote the level of farm household income and alleviate the intra-rural income disparity, with this finding still holding after addressing the potential endogeneity problem and conducting robust-type tests. (2) Rural e-commerce has the most pronounced income-generating effect on low-income households in the southern region; participation in rural e-commerce has a more “center-expanding” effect on households in the secondary education and high material capital groups. (3) Saving production and operation costs, shortening the product circulation chain, and improving access to information are channels through which rural e-commerce affects households’ income. It is recommended to actively promote the deep integration and development of rural e-commerce in rural areas, establish a sound mechanism for bridging the “digital divide”, encourage e-commerce “leaders” to build a perfect industrial chain, and guide smallholders to integrate into the rural e-commerce industrial chain to enjoy the digital dividend.